87 President Oral Presentation Pick: Oral Microbiota Populations of Adult Dogs Consuming Dental Chews Demonstrated to Reduce Dental Plaque and Calculus. (30th November 2020) - Oba, Patrícia M; Carroll, Meredith; Alexander, Celeste; Lye, Lynn; Somrak, Amy; Keating, Stephanie; Sage, Adrianna; Swanson, Kelly S
Abstract: Microbiota play a prominent role in canine periodontal disease, but little is known about the oral microbial community of dogs. We aimed to determine the differences in oral microbiota of dogs consuming dental chews demonstrated to improve oral health outcomes. Twelve adult dogs were used in a replicated 4x4 Latin square design consisting of 28-day periods. Control (CT) dogs consumed diet only, with treatment groups receiving one of three dental chews (BC, DL and GR). At baseline, teeth were cleaned. Teeth were scored for plaque, calculus, and gingivitis at the end of each period by a veterinary dentist blinded to treatments. Breath samples were measured for sulfur compounds throughout each period. Plaque [supragingival (SUP) and subgingival (SUB) plaque] and saliva (SAL) samples were collected for microbiota analysis. Total DNA from saliva and plaque samples was extracted, with 16S rDNA V4 region gene amplicons subjected to Illumina sequencing. Data were analyzed using QIIME 2 and SAS. CT dogs had a higher pocket score, breath sulfur concentrations, and plaque and calculus scores compared to those given chews. Bacterial species richness was highest for CT, with unweighted and weighted PCoA plots showed a clustering of CT dogs vs. those given chews. For all sample types, CT dogs had higher relative abundance of potential pathogenic bacteria (Porphyromonas, Tannerella, and Treponema) and lower relative abundance of bacterial genera associated with oral health (Neisseria, Corynebacterium, Bergeyella, and Moraxella) compared to those given chews. DL reduced Porphyromonas in SUP and SUB samples. DL and GR reduced Treponema in SUP samples. DL increased Corynebacterium in all sample types. BC increased Corynebacterium in SAL samples. DL and GR increased Neisseria and Moraxella in SAL samples. Our results suggest that the dental chews tested beneficially shifted oral microbiota populations, which were associated with improvements in plaque and calculus scores.